Report on business attachment with The Insurance Corporation of Singapore. - Tey, Chee Keong. (2009)
The importance of working experience has always been recognized but there was no way a student could have obtained it through classroom lessons, this problem was solved with the implementation of the business attachment programme. For some students the job nature of the attachment might not be related to the course of study but still there is much to learn. As was noted by employers, the leaving of a job is usually due to the inability to communicate well and maintain good working relationships rather than technical incompetence. So the development of good communication skills should not be neglected and the attachment programme has definitely provided the necessary environment.